Transparência e democracia: os avanços e limites na área tributária no Brasil no período pós 1995 - Araujo, Wilson José De (2004)
This study has the purpose analyze the Brazilian tax system from the point of view of its transparency, arguing this subject in the context of state reforms and based upon democratic principles. Under this perspective the tax system is analyzed focusing on its transparency as a requirement of the democracy, in the relationship between Treasury departments (State) and their contributing (citizens). Taking as a reference the measures adopted from 1995 which had as objective to endow the public administration with better instrument of management, aiming at the increase of the collection of the tributes, at the same time searching to put to the disposal of the society best forms of access to the apparatus tributary. The main reference used is the VAT (ICMS) adopted in the state of São Paulo. Justify this study because, inside the process of redefinition of the role of the Estate, tax system is one of the less studied fields under the democratic aspect, although it be also among the ones that most concerns Brazilian society.